The Moderating Effect of Social Participation on the Relationship between Urban Green Space and the Mental Health of Older Adults: A Case Study in China - Yuan Zheng; Bin Cheng; Letian Dong; Tianxiang Zheng; Rong Wu (Land, 2024)
China is experiencing unprecedented urbanization and aging. Previous studies mostly ignored the internal mechanism of the effect of urban green space on the mental health of older adults. Consequently, the relationship between social participation in urban green spaces and mental health remains uncertain. Therefore, this study explored the impact of urban green spaces, social participation, and other factors on the mental health of older adults and investigated the mechanisms of these effects. This study used linear regression models and conducted a moderating effect analysis using data from the 2018 China Labor Dynamics Survey, comprising 3501 older adults in 146 cities in China. Furthermore, we analyzed differences between solitary and non-solitary older adults. The results indicated that urban green space, road density, physical health, history of hospitalization, subjective well-being, and economic satisfaction significantly affected mental health. Social participation played a significant positive moderating role in the connection between green spaces and mental health among older adults. For solitary older adults, social participation weakened the positive impact of green spaces on mental health; for non-solitary older adults, social participation enhanced the positive impact of green spaces on mental health. These findings could contribute to the future construction of aging-friendly cities in China and help optimize urban construction and strategies for building healthy environments.